2005
DOI: 10.1007/s00170-004-2411-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of tool wear and surface finish in hard turning

Abstract: Hard turning is a profitable alternative to finish grinding. The ultimate aim of hard turning is to remove work piece material in a single cut rather than a lengthy grinding operation in order to reduce processing time, production cost, surface roughness, and setup time, and to remain competitive. In recent years, interrupted hard turning, which is the process of turning hardened parts with areas of interrupted surfaces, has also been encouraged. The process of hard turning offers many potential benefits compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(38 citation statements)
references
References 18 publications
1
31
0
Order By: Relevance
“…Researchers have used the Taguchi parameter design method for the purpose of optimizing turning parameters for minimizing surface roughness and to obtain dimensional accuracy and long life of the cutting tool [13][14][15][16][17] and some success has been reached [18][19][20][21][22]. Across these studies, it was Tamizharasan et al [23] who presented a rather skeptical finding that the depth of cut and the feed rate have negligible and little respective effect on the surface finish, which presents an opportunity for a reassessment of this finding.…”
Section: Brief Review Of the Machining Studies Using Taguchi Methodsmentioning
confidence: 99%
“…Researchers have used the Taguchi parameter design method for the purpose of optimizing turning parameters for minimizing surface roughness and to obtain dimensional accuracy and long life of the cutting tool [13][14][15][16][17] and some success has been reached [18][19][20][21][22]. Across these studies, it was Tamizharasan et al [23] who presented a rather skeptical finding that the depth of cut and the feed rate have negligible and little respective effect on the surface finish, which presents an opportunity for a reassessment of this finding.…”
Section: Brief Review Of the Machining Studies Using Taguchi Methodsmentioning
confidence: 99%
“…The authors also have detected significance of radial force and feed rate in this paper. Tamizharasan et al (2006) proposed that as an alternative to grinding, the hard turning produced better surface finish, lower flank wear rate and high material removal on the selected crank pin material by low content CBN tool. concluded that the surface roughness was low by CBN at high cutting speed but the flank wear was high during machining stainless steel (45-55 HRC).…”
Section: Review Of Literature and Objectivesmentioning
confidence: 99%
“…Several experimental studies have been performed to investigate the influence of cutting parameters (cutting speed, feed and depth of cut), machining time, tool geometry, workpiece hardness, tool materials, different coatings on machinability characteristics like surface roughness, cutting forces and tool flank wear with various workpiece materials (MDN 250, AISI 4340, 4140, 52100, 6150, D2, D3, H10, H11 and H13 die steel) in hard turning for process optimization and machining performance prediction through experimental methods (Tamizharasan et al 2006;Lalwani et al 2008;Hosseini et al 2016;Das et al 2016), mathematical models (Singh & Rao 2007;Al-Ahmari 2007;Ozel et al 2007;Sieben et al 2010;Asiltürk & Çunkaş 2011) and statistical analysis Caydas 2010;Bouacha et al 2010;Nabil et al 2012). Aslan et al (2007) conducted an optimization study by machining a hardened AISI 4140 grade (63 HRC) steel with Al 2 O 3 + TiCN mixed ceramic inserts in order to analyze the effect of cutting parameters (cutting speed, feed rate and depth of cut) on surface roughness and flank wear by employing Taguchi technique, ANOVA and regression analysis.…”
Section: Introductionmentioning
confidence: 99%